Optimal Pricing Strategies and Computer Simulation of DCSC with Fairness Preference and Risk-Aversion Members - Guangxing Wei; Qiang Lin (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Firstly, this paper develop a basic two-echelon DCSC model as the comparative benchmark in the general case of the stochastic demand effected by the service level of the retailer, where the manufacturer's optimal direct price, wholesale price and the retailer's optimal retail price were achieved under Stackelberg game. Then, through incorporate the fairness preference and risk-aversion characteristics into the basic DCSC model, the manufacturer's optimal direct price, wholesale price and the retailer's optimal retail price were obtained under Stackelberg game. At last, by the numerical simulation, the effect of fairness preference and risk aversion level on the optimal pricing strategies and utility of DCSC was examined respectively. The results show that for a DCSC with fairness preference and risk aversion members, the manufacturer and the retailer will choose a reduced price to avoid income risk even if the market demand is stable. Although the decision makers can realize the improvement of their own utility in some circumstances, the utility of the whole supply chain always presents decreasing.  DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3686